Curriculum Management Implementation Strategies in Improving the Quality of Madrasah Education - Afifah Hidayati; Jalaludin Jalaludin; Mukhamad Najikh; Mukhammad Sultan Alikhan (Indonesian Journal of Education and Social Studies, 2025)
Curriculum management plays a central role in shaping the quality and character of Islamic education in madrasah institutions. This study aims to analyze the implementation of curriculum management and its effectiveness in improving educational quality through the integration of religious and national academic standards. Using a qualitative case study approach, data were collected through in-depth interviews with school leaders, teachers, and staff, direct classroom observation, and document analysis. The results indicate that curriculum planning, implementation, and evaluation are conducted collaboratively using the CIPP (Context, Input, Process, Products) model, emphasizing harmony between cognitive, affective, and spiritual domains. Regular evaluation cycles enhance the adaptability and relevance of learning materials to students’ needs. The study contributes a contextualized model of value-based curriculum management that strengthens the alignment between institutional vision and classroom practices. The findings highlight the importance of systematic, reflective, and integrative curriculum evaluation for sustainable educational quality improvement.